Pengaruh Penerapan Metode Bermain Terhadap Peningkatan Kreativitas Dan Kemampuan Motorik Kasar Anak TK - Halimatus Zahro; Rudy Sumiharsono; Eges Triwahyuni (LP. Ma'arif Janggan Magetan, 2023)
The purpose of the research was to find out whether using the playing method could increase the creativity and gross motor skills of Group A & B students at Dewi Sartika Glenmore Islamic Kindergarten. Variable X (Playing method) has 4 indicators, Y1 (Increasing Creativity) has 5 indicators. Variable Y2 (Gross Motor Ability) contains 7 indicators. The research design uses causal quantitative. The method for determining areas is purposive area sampling. The research population for population research techniques was 36 children from groups A and B. Data collection techniques: 1) observation, 2) interviews, 3) documentary. The results of the interview are then processed into several instrument tests from validity and reliability tests, then classic assumption tests including normality tests, homogeneity tests, autocorrelation tests, and heteroscedasticity tests, and finally hypothesis tests which include t tests and F tests. against Y1 sig<0.05 (0.000<0.05), X against Y2 sig<0.05(0.001<0.05), F . So it can be concluded that the playing method has an effect on increasing creativity and gross motor skills.